2009
DOI: 10.1073/pnas.0810325105
|View full text |Cite
|
Sign up to set email alerts
|

Two-step oligoclonal development of male germ cells

Abstract: During mouse development, primordial germ cells (PGCs) that give rise to the entire germ line are first identified within the proximal epiblast. However, long-term tracing of the fate of the cells has not been done wherein all cells in and around the germ-cell lineage are identified. Also, quantitative estimates of the number of founder PGCs using different models have come up with various numbers. Here, we use tetrachimeric mice to show that the progenitor numbers for the entire germ line in adult testis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…In the adult testis of these mice, the number of independent colors in germline clones was two or three, which by Poisson distribution is consistent with only four germline stem cells separating from the epiblast somatic cells (13). The adult testis contained dozens of adjacent seminiferous tubules of the same color, demonstrating that single germline stem cells are capable of inhabiting many adjacent seminiferous tubules.…”
Section: Clonal Competitions Of Mouse Germline Stem Cells In the Formmentioning
confidence: 56%
See 1 more Smart Citation
“…In the adult testis of these mice, the number of independent colors in germline clones was two or three, which by Poisson distribution is consistent with only four germline stem cells separating from the epiblast somatic cells (13). The adult testis contained dozens of adjacent seminiferous tubules of the same color, demonstrating that single germline stem cells are capable of inhabiting many adjacent seminiferous tubules.…”
Section: Clonal Competitions Of Mouse Germline Stem Cells In the Formmentioning
confidence: 56%
“…We propose that genetic changes occur in most of the cells, and most will not give rise to viable germline-derived sperm. Others have noted that the time period in which we see the maximal cell death coincides with the movement within the germline of transposable DNA elements, many of which are the survivors of horizontally transmitted retroviruses that have invaded the germline (13,14). During this movement, copies of particular retrotransposons are made and insert throughout the genome, creating, for the most part, interruptions of genes and, perhaps, enhancers retained in the transposable element.…”
Section: Speculation On the Basis Of Germline Stem Cell Loss During Tmentioning
confidence: 99%
“…Scaldaferri et al set (McLean et al, 2003). It has been recently suggested that adult SSCs are already selected among PGCs before 13.5 dpc (Ueno et al, 2009), but the molecular mechanisms underlying SSC fate commitment remain obscure.…”
Section: Abstract: Testis Development Spermatogonial Stem Cell Sidmentioning
confidence: 99%
“…Scaldaferri et al set (McLean et al, 2003). It has been recently suggested that adult SSCs are already selected among PGCs before 13.5 dpc (Ueno et al, 2009), but the molecular mechanisms underlying SSC fate commitment remain obscure.Previous studies in the mouse have shown that SSCs can be identified by their ability to efflux dyes such as Hoechst 33342 (Falciatori et al, 2004;Lassalle et al, 2004). This ability, defined as the "side-population" (SP) phenotype, is common to several stem/progenitor cell types (Challen and Little, 2006) and relies on the activity of ATP-binding cassette (ABC) transporter superfamily, including multidrug resistance 1 (Mdr1a/1b, mouse; MDR1, human) and breast cancer resistance protein 1 (Bcrp1, mouse; ABCG2 human) (Bunting et al, 2000;Zhou et al, 2001).…”
mentioning
confidence: 99%
“…It seemed likely that tissue stem cell biology could account for the programmed life span and could reveal the genetic units of intraorganismal natural selection of stem cell lineages (189)(190)(191). These studies were the basis for our experiments to test for a diversity of competing HSCs in aging, a diversity of germline stem cells in testis and ovary development in mice (192), and the concept of clonal competitions in cancers (161,(193)(194)(195)(196)(197)(198)(199).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%